2014
DOI: 10.1002/ejic.201402554
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Bis(organoamino)phosphanes with Aluminum(III) Compounds: Straightforward Access to Diiminophosphinates by Means of Hydrogen‐Atom Migration – An Experimental and Theoretical Study

Abstract: The reactivity of bis(organoamino)phosphanes PhP(NHR) (NHRЈ) (1a-1c, in which R, RЈ = tBu for 1a; tBu, Dip for 1b; and Ph for 1c; Dip = C 6 H 3 -2,6-iPr 2 ) and tBuP(NHDip) 2 (1d) with Me 3 Al was investigated. The reaction of 1a or 1b gave in the first step compounds [PhP(NHR)(NRЈ)]AlMe 2 (in which R, RЈ = tBu for 2a; tBu, Dip for 2b) as a result of methane elimination that upon heating underwent nitrogen-to-phosphorus hydrogen-atom migration under the formation of diiminophosphinates [Ph(H)P(NR)(NRЈ)]AlMe 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Recently, we have demonstrated that related aluminum amide [PhP(NHt-Bu)(Nt-Bu)]AlMe 2 smoothly underwent a tautomeric hydrogen shift upon heating with quantitative formation of the phosphinate [Ph(H)P(Nt-Bu) 2 ]AlMe 2 . 7 Analogously, heating of a THF solution of 5 (70 °C) led to magnesium phosphinate [Ph(H)P(Nt-Bu) 2 ] 2 Mg (7) (Scheme 1) as monitored and judged using 1 H and 31 P NMR spectroscopy. However, this tautomeric shift is significantly slower than in the case of the aluminum derivative (less than 10% conversion after 5 days) and, more importantly, prolonged heating of 5 resulted in the formation of numerous side-products.…”
Section: Syntheses and Nmr Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have demonstrated that related aluminum amide [PhP(NHt-Bu)(Nt-Bu)]AlMe 2 smoothly underwent a tautomeric hydrogen shift upon heating with quantitative formation of the phosphinate [Ph(H)P(Nt-Bu) 2 ]AlMe 2 . 7 Analogously, heating of a THF solution of 5 (70 °C) led to magnesium phosphinate [Ph(H)P(Nt-Bu) 2 ] 2 Mg (7) (Scheme 1) as monitored and judged using 1 H and 31 P NMR spectroscopy. However, this tautomeric shift is significantly slower than in the case of the aluminum derivative (less than 10% conversion after 5 days) and, more importantly, prolonged heating of 5 resulted in the formation of numerous side-products.…”
Section: Syntheses and Nmr Studiesmentioning
confidence: 99%
“…6 Recently, we have successfully applied this synthetic strategy in the case of aluminum(III) complexes. 7 We report herein on the reactivity of analogous phosphanes 1-3 (Fig. 2) with magnesium(II) compounds.…”
Section: Introductionmentioning
confidence: 97%
“…37 In this regard, the cationic complexes are also of great interest due to increased electrophilicity resulting from the cationic charge, possibly enhance the substrate coordination and activation. 32,38 Although achiral iminophosphonamides have a rich coordination chemistry, the structurally characterized group 13 metal complexes are limited to a few NPN ligand backbones such as [Ph 2 P(NSiMe 3 ) 2 ] − , 39 42 [Ph 2 P(NDip) 2 ] − , 43 and [rac-[trans-1,2-C 6 H 12 {NP(Ph 2 )N(Ar)} 2 ] − (where Ar = 2,4,6-Me 3 C 6 H 2 or 2,6-Me 2 C 6 H 3 ). 44 To the best of our knowledge, the coordination chemistry of group 13 metal complexes with the chiral iminophosphonamide ligand was not investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported on the complexes, LBHCl, LB(Ph)Cl, LBH 2 , LB(Ph)H, [LAlH 2 ] 2 , LAlMe 2 , LMCl 2 (M = B, Al Ga), LAlMe(C 6 F 5 ) with lighter group 13 elements (L=(2,6‐iPr 2 C 6 H 3 N)P(Ph 2 )(NtBu)). Dostál and co‐workers have published on [PhP(H)(NPh) 2 ]AlMe 2 , [PhP(H)(NtBu) 2 ]AlCl 2 , [PhP(H)(N‐2,6‐iPr 2 C 6 H 3 )(NtBu)]AlCl 2 , [tBuP(H)(N‐2,6‐iPr 2 C 6 H 3 ) 2 ]AlCl 2 …”
Section: Introductionmentioning
confidence: 99%
“…In view of very limited number of examples of structurally characterized iminophosphonamides of group 13 elements we are interested to explore the syntheses and properties of their complexes. Prior to the present work, the groups of Roesky, Hill, Singh, and Dostál have reported on the structurally characterized iminophosphonamide complexes of lighter group 13 elements (B and Al). These are limited to a few aluminum complexes, [Ph 2 P(NSiMe 3 ) 2 ]AlX(Cl) (X = Cl, Me), [Ph 2 P(NSiMe 3 ) 2 ]Al(NMe 2 ) 2 , [Ph 2 P(NSiMe 3 ) 2 ] 2 AlH reported by Roesky .…”
Section: Introductionmentioning
confidence: 99%